Physical activity during pregnancy and its association with postpartum depression, weight retention, and quality of life – a narrative review - Łuczak, Karolina; Malicka, Natalia; Tłustochowicz, Katarzyna; Krajewska, Agnieszka; Dębczak, Julia; Korzeniewska, Agnieszka; Kowalik, Adrianna; Polkowska, Wiktoria; Korba, Magdalena (Quality in Sport, 2026)
Background: Regular physical activity during pregnancy is recommended due to its beneficial effects on maternal and fetal health. In recent years, increasing attention has been directed toward potential long-term benefits of antenatal physical activity extending into the postpartum period. However, evidence regarding its influence on postpartum mental health, body weight outcomes, and quality of life remains heterogeneous. Aim: The aim of this narrative review was to synthesize evidence on the association between physical activity during pregnancy and selected maternal outcomes after childbirth, focusing on postpartum depressive symptoms, postpartum weight retention, and maternal quality of life. Materials and methods: A narrative literature review was conducted using the PubMed database. Articles published between 2000 and 2026 were identified using keywords and MeSH terms related to physical activity, exercise, pregnancy, postpartum outcomes, depression, gestational weight gain, postpartum weight retention, and quality of life. Randomized controlled trials, cohort studies, systematic reviews, meta-analyses, umbrella reviews, and clinical guidelines were included. Results: Evidence from systematic reviews and meta-analyses suggests that physical activity during pregnancy may reduce postpartum depressive symptoms, particularly in structured exercise interventions. Prenatal physical activity may also contribute to lower postpartum weight retention by limiting excessive gestational weight gain. Limited evidence indicates a positive association between prenatal physical activity and postpartum quality of life. Conclusions: Physical activity during pregnancy may provide benefits extending into the postpartum period, particularly for maternal mental health and weight outcomes. Current evidence supports promoting regular and safe physical activity during pregnancy as part of preventive health strategies.